Are Market GM Plants an Unrecognized Platform for Bioterrorism and Biocrime? - Mueller, Siguna (Frontiers in Bioengineering and Biotechnology, 2019)
This article discusses a previously unrecognized avenue for bioterrorism and biocrime. It is suggested that new gene editing technologies may have the potential to create plants that are genetically modified in harmful ways, either in terms of their effect on the plant itself or in terms of harming those who would consume foods produced by that plant. While several risk scenarios involving GMOs—such as antibiotic resistant pathogens, synthetic biology, or mixing of non-GMO seeds with GMO seeds—have previously have been recognized, the new vulnerability is rooted in a different paradigm—that of clandestinely manipulating GMOs to create damage. The ability to actively inflict diseases on plants would pose serious health hazards to both humans and animals, have detrimental consequences to the economy, and directly threaten the food supply. As this is the first study of this kind, the full scope and impact of suck attacks—especially those involving the intended misuse of technologies such as gene-drives—merits further investigation. Herein, the plausibility of some of the new risks will be analyzed by, (1) Highlighting ownership and origination issues (esp. of event-specific GM-plants) as unrecognized risk factors; (2) Investigating the unique role of GMOs, why—and how—certified GMOs could become a new venue for such attacks; (3) Analyzing possible dual-use potentials of modern technologies and research oriented toward the advancement of GMOs, plant breeding and crop improvement. The identification and analysis of harmful genetic manipulations to utilize (covertly modified) plants (GMOs and non-GMOs) as an attack vector show that these concerns need to be taken seriously, raising the prospect not only of direct harm, but of the more likely effects in generating public concern, reputational harm of agricultural biotechnology companies, law-suits, and increased import bans of certain plants or their derived products.